A bibliography of Greek New Testament manuscripts - Elliott, J. K. 1943-2024 (Cambridge Univ. Press, 2000)
Facsimiles, photographic reproductions, collations, and studies of the textual character of many of the 5,000 or so manuscripts of the Greek New Testament have been published, but it is only with this book, first published in 2000, that a much-needed bibliography of them has been made available. This considerably expanded and revised edition of J. K. Elliott's 1989 A Bibliography of Greek New Testament Manuscripts marks a substantial increase in the number of titles and references. Some 5,000 new entries have been added, thereby doubling the size of the First Edition. The titles of books and articles are predominantly those published in the last 150 years. The titles are set out in the customary categories of papyri, majuscules, minuscules and lectionaries as classified in the conventional Gregory-Aland register
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Erscheinungsjahr des E-Books: 2009
Keywords: Bible / New Testament / Manuscripts, Greek / Catalogs; Bibel -- Neues Testament; Bibel; Bibliografie; Griechisch; Handschrift; Katalog